2018
DOI: 10.1128/aac.01968-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of the Siderophore Cephalosporin, Cefiderocol, against Carbapenem-Nonsusceptible and Multidrug-Resistant Isolates of Gram-Negative Bacilli Collected Worldwide in 2014 to 2016

Abstract: The in vitro activity of the investigational siderophore cephalosporin, cefiderocol (formerly S-649266), was determined against a 2014–2016, 52-country, worldwide collection of clinical isolates of carbapenem-nonsusceptible Enterobacteriaceae (n = 1,022), multidrug-resistant (MDR) Acinetobacter baumannii (n = 368), MDR Pseudomonas aeruginosa (n = 262), Stenotrophomonas maltophilia (n = 217), and Burkholderia cepacia (n = 4) using the Clinical and Laboratory Standards Institute (CLSI) standard broth microdiluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
174
3
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(191 citation statements)
references
References 23 publications
10
174
3
4
Order By: Relevance
“…For A. baumannii our MIC 90 of 1 mg/liter was in agreement with the MIC 90 values of 1 and 2 mg/liter, respectively, reported by Ito et al (10) and Hackel et al (29), while a later publication by Hackel et al reported a higher MIC 90 value of 8 mg/liter (30). The reason for this difference in activity against A. baumannii may be associated with regional differences in the resistance mechanisms of this species.…”
supporting
confidence: 90%
“…For A. baumannii our MIC 90 of 1 mg/liter was in agreement with the MIC 90 values of 1 and 2 mg/liter, respectively, reported by Ito et al (10) and Hackel et al (29), while a later publication by Hackel et al reported a higher MIC 90 value of 8 mg/liter (30). The reason for this difference in activity against A. baumannii may be associated with regional differences in the resistance mechanisms of this species.…”
supporting
confidence: 90%
“…In in vitro studies, cefiderocol was shown to be potent against OXA-23, OXA-40, and OXA-58 as well as NDM-and IMP-producing A. baumannii isolates, with MIC 90 s ranging from 1 to 8 g/ml (35)(36)(37)(38)(39)(40). However, it seems to be less active against some strains of A. baumannii that express OXA-23 and OXA-40 (38,40,41).…”
Section: New Therapeutic Optionsmentioning
confidence: 99%
“…In this study, the antibacterial activity of three compounds belonging to the first-, second-, and third-generation Ga(III) formulations, i.e., GaN, GaM, and GaPPIX, was tested on ESKAPE pathogens in culture media characterized by different iron content, namely Mueller-Hinton broth (MHB), iron-deprived MHB (DMHB) (Hackel et al, 2018 ) and RPMI-1640 tissue culture medium supplemented with 10% complement-free human serum (RPMI-HS), to better mimic the in vivo environment (Antunes et al, 2012 ; Thompson et al, 2012 ; Bonchi et al, 2015 ). ESKAPE bacteria resulted more susceptible to Ga(III) compounds in RPMI-HS than in MHB and DMHB.…”
Section: Introductionmentioning
confidence: 99%